OVERCOMING TURNOVER INTENTION PROBLEMS: DIRECT-INDIRECT MODEL TO IDENTIFY THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT AND JOB SATISFACTION IN SERVICE-BASED ORGANIZATIONS - Azis, Elvira; Prasetio, Arif Partono; Utomo, Kristian Heri (Jurnal Aplikasi Manajemen, 2019)
Current study investigates the direct effect of perceived organizational support on turnover intention and the mediation of job satisfaction in the relation. The turnover intention has become important issues in human resource management. It can cause losses and distraction in the business. The organization needs to identify what are the main factors which contribute or drive an employee to resign. By identifying such factors, they can improve their human resources practices to retain outstanding employees. Perceived organizational support considered havingan important effect on employee regarding their perception towards the organization. Meanwhile, the thoughts of leaving the organization can also develop from a low satisfaction level. The organization must be aware of this condition to retain the best performers. This study used 366 participants from the various organization in West Java and consisted of a manager, supervisor, and officer. We conducted mediation analysis, and the result showed only a small direct effect from perceiving organizational support on turnover intention while job satisfaction mediated the relation. The intervention proves to have a greater impact on reducing the intention. This finding corroborated previous literature and underlined that perceive organizational support and job satisfaction can help an organization in mitigating turnover level.